2020
DOI: 10.1016/j.stemcr.2020.07.015
|View full text |Cite
|
Sign up to set email alerts
|

Mutation-Specific Guide RNA for Compound Heterozygous Porphyria On-target Scarless Correction by CRISPR/Cas9 in Stem Cells

Abstract: Summary CRISPR/Cas9 is a promising technology for gene correction. However, the edition is often biallelic, and uncontrolled small insertions and deletions (indels) concomitant to precise correction are created. Mutation-specific guide RNAs were recently tested to correct dominant inherited diseases, sparing the wild-type allele. We tested an original approach to correct compound heterozygous recessive mutations. We compared editing efficiency and genotoxicity by biallelic guide RNA versus mutant al… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 71 publications
(90 reference statements)
0
4
0
1
Order By: Relevance
“…Future work should be aimed not only at detecting these iCN-LOHs but also at understanding their biological roots and reasons for occurrence as well as biological roots and phenotypic consequences. DSB-free genome editing with single nickase or base editors or nuclease-based gene therapy in iPSC with safe corrected clone sorting might be answers 35 37 .…”
Section: Discussionmentioning
confidence: 99%
“…Future work should be aimed not only at detecting these iCN-LOHs but also at understanding their biological roots and reasons for occurrence as well as biological roots and phenotypic consequences. DSB-free genome editing with single nickase or base editors or nuclease-based gene therapy in iPSC with safe corrected clone sorting might be answers 35 37 .…”
Section: Discussionmentioning
confidence: 99%
“…They lead to disrupted targeted sequences and cause unwanted dysfunctional protein in cell lines and iPSC. 60,61 We demonstrated that uncontrolled indels induced by the NHEJ are very frequent in corrected HEK293T, with a precise genome editing ratio (HDR/NHEJ) of 0.5. Several approaches have been proposed to improve this ratio e.g.…”
Section: Toxicity and Recent Improvements In Gene Editing For Gene Th...mentioning
confidence: 94%
“…This design that avoids genotoxicity with ON-target scarless gene correction should be recommended for recessive diseases with frequent cases of compound heterozygous mutations. 61 In addition to small indels, a single ON-target DSB (without a second DSB at OFFtarget genomic loci) can also lead to interstitial large deletions of several kilobases, symmetrical or not at the targeted site, in mouse hematopoietic progenitors, in human immortalized differentiated cells or in mouse embryos. 63 Recently, larger deletions (up to three hundred kilobases) in mouse zygote were reported.…”
Section: Toxicity and Recent Improvements In Gene Editing For Gene Th...mentioning
confidence: 99%
“…Accordingly, syngeneic disease and non-disease models can be generated by either correcting coagulation deficiency-affected iPSCs or re-creating relevant point mutations, consequently overcoming the obstacle of sample accessibility and experimental variability (Hockemeyer and Jaenisch, 2016;McTague et al, 2021). In addition, the iPSC-based, CRISPR-edited system may allow the modification of a single allele, thereby recapitulating the genetic background of a heterozygote (Rabai et al, 2019;Prat et al, 2020). This strategy has been adopted by Luce et al (2021) where they have generated syngeneic disease and disease-corrected models to investigate HB and to pave the way for the next experimental phases, consisting of gene editing and cell-therapy for HB.…”
Section: Hemophilia Bmentioning
confidence: 99%